Implementasi Peranan Advertising Untuk Meningkatkan Penjualan Pada Media Sosial Tiktok - Yuliana, Margaretha Evi; Saputro, Andi; Sutomo, Ervin (CV. ITTC INDONESIA, 2023)
Tiktok is one of the most popular social media platforms. Tiktok offers its users to create short 15-second videos accompanied by music, filters and several other creative features. Tiktok in Indonesia is widely used for creativity and business by users. Lately, the widespread use of social media in the form of the TikTok application. The TikTok application is an application for creating and sharing various short videos in a vertical format, which are played by simply scrolling up or down on the screen. In Indonesia, the community is very interested in the TikTok application, and not a few Indonesians have even become TikTok celebrities. Currently, TikTok users in Indonesia have reached 92.2 million users, as of July 2021 this number has increased. At the start of the pandemic, April 2020 to be precise, TikTok users only reached 37 million user